Aetiology of community-acquired, acute gastroenteritis in hospitalised adults: a prospective cohort study - Werber Dirk; Liesenfeld Oliver; Ignatius Ralf; Schreier Eckart; Kunkel Jan; Stark Klaus; Jansen Andreas; Göbel Ulf B; Zeitz Martin; Schneider Thomas (BMC Infectious Diseases, 2008)
Abstract Background The aetiology of severe gastroenteritis leading to hospitalisation in adults frequently remains unclear. Our objective was to study the causes and characteristics of community-acquired, acute gastroenteritis in adult hospitalized patients to support the clinical management of these patients. Methods From August 2005 to August 2007, we conducted a prospective cohort study among patients ≥18 y hospitalized with community-acquired gastroenteritis in a university hospital in Berlin, Germany. Stool specimens were examined for 26 gastrointestinal pathogens, supplemented by serologic tests for antibodies to Campylobacter spp., Yersinia spp., and Entamoeba histolytica. Patient data on demographics and clinical presentation were recorded and analyzed. Coexisting medical conditions were assessed using the Charlson Comorbidity Index score. Results Of 132 patients presenting with acute community-acquired gastroenteritis, 104 were included in the study. A non-infectious aetiology was diagnosed in 8 patients (8%). In 79 (82%) of the remaining 96 patients at least one microorganism was identified. Campylobacter spp. (35%) was detected most frequently, followed by norovirus (23%), Salmonella spp. (20%), and rotavirus (15%). In 46% of the patients with Campylobacter spp. infection, the diagnosis was made solely by serology. More than one pathogen was found in seventeen (22%) patients. Simultaneous infection was significantly more likely in patients with rotavirus and salmonella infections (RR 3.6; 95% CI: 1.8–7.4; RR 2.5; 95%CI: 1.2–5.5). Length of hospital stay (median: 5.5 days) was independent of the pathogen, but was associated with coexisting medical conditions (OR 4,8; 95%CI:2,0–11,6). Conclusion Known enteric pathogens were detected in 82% of adult patients who were hospitalized with acute gastroenteritis. We found that currently used culture-based methods may miss a substantial proportion of Campylobacter infections, and additional serological testing for Campylobacter should be considered. Viral infections emerged as an important cause of severe gastroenteritis in adults, and viral-bacterial co-infections in adults are probably underrecognized so far. The presence of coexisting medical conditions – but not the etiological agent – was a predictor for the duration of the hospital stay.